Late Middle Palaeolithic assemblages with flake cleavers in the western Pyrenees: The Vasconian reconsidered - Deschamps, Marianne (2018)
The analysis of several lithic assemblages with flake cleavers and bifaces from sites attributed to MIS 5 and 3 in the western Pyrenees provides the basis for a new chronological and typo-technological characterisation of the region's late Middle Palaeolithic record. Previously assigned to the Vasconian based strictly on typological criteria, a certain degree of variability evident between the analysed assemblages likely indicates different occupation types. However, broad typo-technological traits reflecting a common regional tradition can be identified and are discussed against the backdrop of the regional diversity and cultural geography of late Middle Palaeolithic industries dated to around 50 ka BP. This ‘regionalisation’ of lithic techno-complexes may also have important ramifications for the socioeconomic organisation and demographic dynamics of late Middle Palaeolithic human groups.